Fruity garden - Ismail, Nor Atiah; Egoz, Shelley; Cushman, Grant (University Putra Malaysia, 2012)
Research in fruity garden investigated the meanings invested in the altered landscapes in low, medium and high-cost urban residential areas. It was found that the majority of urban residents contested the existing homogenous landscape comprising of ornamental shade trees and ground cover. This research relied on the rural cultural landscapes of the Malay, Chinese and Indian communities as one of the theoretical frameworks underpinning landscape alteration undertaken by rural-urban